Insecticidal activity of the essential oil of Schinus areira against Rhipibruchus picturatus (F.) (Coleoptera: Bruchinae), and its inhibitory effects on acetylcholinesterase - Tapia Mattar, Valeria (2022)
During the storage of Prosopis alba pods, substantial quantitative and qualitative losses were observed. One of the main factors is the seed beetle Rhipibruchus picturatus. A key strategy to develop new pest control management is the use of essential oils (EOs) due they are efficient, less toxic, and less persistent in the environment compared to synthetic pesticides. In this context, seeds and leaves of Schinus areira L. (Anacardiaceae) EOs and Citrus spp. EO were studied in the present work. In the leaves of S. areira EO, 1-epi-cadinol, sesquiterpenoid alcohol, was the major compound. On the other hand, the main compounds of the EO extracted from S. areira seeds are the monoterpenes sabinene, and α-pinene. Finally, in the Citrus EO, limonene is the principal component. The three EOs obtained exhibited insecticidal activity against R. picturatus, being the first report of the use of EOs against this insect pest. The best insecticidal results were obtained with the leaves of S. areira EO. Moreover, this EO inhibits the acetylcholinesterase enzyme in vitro assays. Molecular docking studies on acetylcholinesterase (AChE) suggest that the main components of the leaves of S, areira EOs, bind to the active site of the enzyme, in good agreement with in vitro competitive inhibition against AChE observed for this EO. The data obtained demonstrate the potential use of Schinus areira EOs in the development of new storage pest control strategies.